Sulphydryl reactivity of the HLA-B27 epitope: accessibility of the free cysteine studied by flow cytometry. Issue 4 (April 1992) - MacLean, L; Macey, M; Lowdell, M; Badakere, S; Whelan, M; Perrett, D; Archer, J
Abstract : HLA-B27 has an unpaired cysteine on or near its serologically defined spondylitis associated epitope, and it has been argued that its sulphydryl side chain may be chemically reactive. In a previous study it was shown that chemical treatment of HLA-B27 cells with the sulphydryl binding agent p-chloromercuriphenylsulphonic acid (pCMPSA) specifically reduced binding of antibodies to HLA-B27 by up to 80%, as measured in a cellular enzyme linked immunosorbent assay (CELISA). The effect of sulphydryl blockade on intact B27 cells was investigated using flow cytometry. Compared with the CELISA, inhibition required higher concentrations of pCMPSA, and the degree of inhibition produced by a greater than or equal to 30 microM solution of pCMPSA as measured by flow cytometry (median 28.9%) was significantly lower than that measured by CELISA (median 73.6%; p = 1.6 x 10(-6)). Analysis of unfixed, cell surface HLA-B27 by flow cytometry suggests that on most B27 molecules the unpaired sulphydryl site is not available. On the basis of this evidence for modification after translation, a new 'altered self' hypothesis is proposed for the part which HLA-B27 plays in inflammatory disease.